Twice lived - West, Joma, 1986- (Tordotcom, Tor Publishing Group, 2024)
"There are two Earths. Perfectly ordinary and existing in parallel. There are no doorways between them, no way to cross from one world to another. Unless you're a shifter. Canna and Lily are the same person but they refuse to admit it. Their split psyche has forced them to shift randomly between worlds - between lives and between families - for far longer than they should. But one mind can't bear this much life. It'll break under the weight of it all. Soon they'll experience their final shift and settle at last in one world, but how can they prepare both families for the eventuality of them disappearing forever?"--